Geodynamics Based on Solidification of Liquid/Molten Substances in the Earth’s Interior - Li, Xin; Tao, Mingjiang; He, Duanwei (Frontiers in Earth Science, 2022)
Since the formation of the Earth, it has experienced a process of cooling from molten magma to present layer structure. The Earth as a whole is constantly radiating heat to outer space, and the liquid substances inside will continue to solidify, releasing heat and causing changes in pressure and density. Constrained by the rigid lithosphere, the change in density associated with the solidification in the interior of the Earth will result a reduction in the pressure at the bottom of the crust and the support to the rigid lithosphere. Under the effect of gravity, the interaction between tectonic plates keeps increasing, local stress accumulation will eventually exceed the strength of rock, causing mechanical structure of the crust lithosphere unstable. The Earth adjusts itself to new mechanical equilibrium by releasing accumulated stress through geological events such as earthquakes. The above process is an iterative process. In this study, we group three sets of observation (GPS data, length of day data, and the latent heat of Earth solidification) and aim to showing all these observations are consistent with the assumption that liquid solidification causes changes in density and volume in the Earth’s interior. The results show that the volume change obtained by the internal solidification is consistent with the overall observation results from the external. Mechanical analysis indicates that the solidification of the internal liquid substances leads to the collapse of Earth’s volume, causing the intensification of plate interaction, leading the large plate movement and triggering earthquakes are reasonable. In conclusion, the solidification of liquid substances in the Earth's interior is the main power source for the movement of plates.